A circumbinary planet in orbit around the short-period white dwarf eclipsing binary RR cae - Qian, S. B. (2012)
By using six newly determined mid-eclipse times together with those collected from the literature, we have found that the observed minus calculated (O-C) curve of RR Cae shows a cyclic change with a period of 11.9yr and an amplitude of 14.3 s while it undergoes an upward parabolic variation [revealing a long-term period increase at a rate of Ṗ = +4.18(±0.20) × 10 -12]. The cyclic change was analysed for the light-travel-time effect that arises from the gravitational influence of a third companion. The mass of the third body was determined to be M 3sin i'= 4.2(± 0.4)M Jup, suggesting that it is a circumbinary giant planet when its orbital inclination is larger than 17°.6. The orbital separation of the circumbinary planet from the central eclipsing binary is about 5.3(± 0.6) au. The period increase is opposite to the changes caused by angular momentum loss via magnetic braking or/and gravitational radiation; and it cannot be explained by the mass transfer between both components because of its detached configuration. These indicate that the observed upward parabolic change is only a part of a long-period (longer than 26.3yr) cyclic variation, which may reveal the presence of another giant circumbinary planet in a wide orbit.